Characterization and Modeling of Anodic Oxide Films on a Ti Alloy in Fluoride-Containing Electrolyte. Issue 12 (31st August 2020) - Betova, Iva; Bojinov, Martin; Karastoyanov, Vasil; Slavcheva, Evelina
Abstract : The anodic oxidation of a titanium alloy ( β -21S) in ethylene glycol—water—fluoride solution is studied by chronoamperometry, photocurrent and electrochemical impedance measurements in a wide range of applied potentials. The composition of the surface oxides is estimated by X-ray photoelectron spectroscopy. Data on pure Ti are presented for comparative purposes. All the experimental data are successfully described by a kinetic model previously proposed for anodic oxidation of Ti with bilayer formation. A three-step regression procedure is used to estimate the values of kinetic and transport parameters of electrochemically detectable reaction steps. The effect of alloying elements (Mo and Nb) is discussed in terms of the formation of non-stoichiometric TiO2 containing significant amounts of Mo(V), Mo(VI) and Nb(V) substitutional ions.